Long‐lived deformation in the southern Mississippi Embayment revealed by high‐resolution seismic reflection and sub‐bottom profiler data. Issue 3 (24th March 2015) - Hao, Yanjun; McIntosh, Kirk; Magnani, Maria Beatrice
Abstract Three high‐resolution seismic reflection profiles and two sub‐bottom profiler sections acquired along the Mississippi River in southern‐Central U.S. image deformation in post‐Paleozoic sediments. The northernmost profile images two faults offsetting Cretaceous through at least Eocene Cane River reflectors, interpreted to strike northwest and to be part of the Arkansas River fault zone. The central profile shows a down‐to‐the‐north fault, displacing Cretaceous and Paleocene Midway Group reflectors by ~210 m and ~160 m, respectively. The fault is interpreted as the northern edge fault of the Monroe Uplift, a Late Cretaceous uplift associated with igneous intrusions. The southernmost profile displays a down‐to‐the‐south fault, offsetting Cretaceous and Paleocene‐Eocene Wilcox Group reflectors by ~125 m and ~32 m, respectively. Tilted reflectors in the first 80 m indicate Eocene‐Oligocene activity of the fault, although Quaternary activity cannot be ruled out. Quaternary tectonic activity is proposed for a series of faults that offset shallow (<40 m depth) Eocene sequences and the base of the Quaternary alluvium as imaged on two sub‐bottom profiler sections. These shallow faults are imaged in the vicinity of Holocene earthquake‐induced liquefaction fields, corroborating the evidence for recent tectonic activity in the area. The spatial coincidence of the imaged faults with the inferred location of the Alabama‐Oklahoma transform strongly argues toward a long‐lived influence of this Precambrian continental margin in focusing tectonic activity in the southern U.S. by controlling the reactivation of Triassic‐Jurassic syn‐rift basement structures and guiding the emplacement of Late Cretaceous igneous intrusions and the location of Cenozoic deformation.